SPECIFIC ASPECTS OF JOINT STOCK COMPANIES INCREASING THE VOLUME OF FREE CASH FLOW - Foziljonov Ibrahimjon Sotvoldikhoja ugli (Scholar Express Journals, 2023)
This article presents the scientific and theoretical basis for increasing free cash flow of securities companies based on practical results. This process is carried out using the theories of domestic and foreign economists regarding the calculation of free cash flow. Based on the results of the study, important aspects of increasing a firm's free cash flow are highlighted.
Keywords: free cash flow; net operating profit after taxes; net reinvestments; working capital